The bromodomain-containing protein tBRD-1 is specifically expressed in spermatocytes and is essential for male fertility. - Leser, K.; Awe, S.; Barckmann, B.; Renkawitz-Pohl, R.; Rathke, C. (Biology open, 2012)
By a conserved cellular differentiation process, spermatogenesis leads to formation of haploid sperm for successful reproduction. In Drosophila and in mammals, post-meiotic spermatid differentiation depends on several translationally repressed and stored mRNAs that are often expressed exclusively in the testis through a cell type specific transcriptional program. In Drosophila, the mRNAs of proteins required for post-meiotic chromatin reorganisation, like ProtB and Mst77F, are transcribed in meiotic spermatocytes and subjected to translational repression for days. Transcription of many of these translationally repressed mRNAs depends on testis-specific homologs of TATA box binding protein-associated factors (tTAFs). Here, we identified the testis-specific bromodomain protein, tBRD-1, that is only expressed in primary spermatocytes. Bromodomain proteins are able to recognise and bind acetylated histones and non-histone proteins. We generated tbrd-1 mutant flies and observed that function of tBRD-1 is required for male fertility. tBRD-1 partially colocalised with tTAFs, TAF1 and Polycomb to a Fibrillarin-deficient region within the spermatocyte nucleolus. The nucleolar localisation of tBRD-1 depended on tTAF function but not the other way round. Further, we could show that ectopically expressed tBRD-1-eGFP is able to bind to the interbands of polytene chromosomes. By inhibitor treatment of cultured testis we observed that sub-cellular localisation of tBRD-1 may depend on the acetylation status of primary spermatocytes.